Plasmacytoma of clavicle bone: a case report - Agrawal, Anurag M.; Sharma, Vidhyasagar V.; Halughodu, Amruthavarshini S. (International Journal of Research in Medical Sciences, 2022)
Plasmacytoma refers to a malignant tumor composed of plasma cells, which grows within soft tissue or axial skeleton. These are identical to those in plasma cell myeloma, which appears as a solitary lytic lesion on radiological examination. Primary bone tumor of clavicle are uncommon and likely to be malignant. Systemic issues in multiple myeloma are absent in plasmacytoma which makes it a formidable diagnostic challenge. Authors report a case of sixty-two years old female with progressive swelling around medial end of right clavicle associated with pain and restriction in arm movements. X-ray revealed lytic lesion in medial one-third of clavicle. FNAB revealed small to large plasmacytoid cells. CT Angiography revealed ill-defined heterogenous soft tissue density lesion. Since the mass was near the vascular structure, adjuvant chemoradiotherapy was given. Solitary plasmacytoma of bone (SPB) of medial end of clavicle is rare. Surgery is the mainstay treatment but in inoperable cases, adjuvant therapy may be considered. SPB of clavicle is a unique surgical entity with diagnostic and management challenges.